The independent impact of dementia in patients undergoing percutaneous coronary intervention for acute myocardial infarction. Issue 3 (12th January 2023) - Kodesh, Afek; Bental, Tamir; Vaknin‐Assa, Hana; Talmor‐Barkan, Yeela; Codner, Pablo; Levi, Amos; Kornowski, Ran; Perl, Leor
Abstract: Background: Although age and frailty are associated with worse prognoses for patients who undergo percutaneous coronary intervention (PCI), little is known regarding the independent impact of dementia. Hypothesis: The aim of this study was to evaluate the association between dementia and outcomes for patients with acute myocardial infarction (AMI). Methods: Consecutive patients with ST‐elevation or non‐ST elevation MI who had undergone PCI as part of our AMI registry were included in this study. We compared outcomes within the 1‐year period of their PCI, including death and major adverse cardiac events (MACE) and corrected for confounders using Cox regression. Results: Of 28 274 patients, 9167 patients who had undergone PCI for AMI were included in this study, 250 with dementia; Mean age (77.4 ± 9.4 in the dementia group vs. 63.6 ± 12.7 in the control), female gender (32.4 vs. 24.2%, p  = .003), diabetes mellitus (54.0 vs. 42.4%, p  < .001) and chronic kidney disease (44.4 vs. 19.3%, p  < .001) were higher. At 12 months, unadjusted rates of death (25.5 vs. 9.8%, p  < .001) and MACE (33.8 vs. 17.6%, p  < .001) were higher for patients with dementia. After standardizing for confounding variables, dementia remained an independent risk factor for death (HR 1.90; CI 1.37–2.65; p  < .001) and MACE (HR 1.73; CI 1.30–2.31; p  < .001), as well as in propensity score matched analysis (HR 1.54; CI: 1.03–2.28; p  < .001 and HR 1.49; CI: 1.09–2.02; p  < .001, respectively). Conclusions: Dementia is an independent predictor of worse outcomes in patients undergoing PCI for AMI. Future intervention and specialized healthcare measures to mitigate this risk is warranted.